Analysis of the Validity and Readability of E-Supplement Based on Problem Based Learning Assissted Augmented Reality to Improving Students’ Critical Thinking Skills - Puspita Diana Arumawati; Ari Yuniastuti; Dyah Rini Indriyanti; Sri Sukaesih (Unnes Science Education Journal, 2025)
This study aims to analyze the validity and readability of Problem Based Learning (PBL)-based e-supplements assisted by Augmented Reality in improving students’ critical thinking skills. Learning by utilizing teaching materials in the form of e-supplements integrated with PBL and Augmented Reality learning models is expected to provide a significant contribution to improving students’ critical thinking skills, as well as providing new insights in developing effective digital teaching materials. This study usedthe research and development (R&D) method but only up to the small-scale trial stage. The subjects of this study were grade XI students of SMA N 6 Surakarta. The data instruments used in this study were media and material validation questionnaires and readability questionnaires. The product validity criteria are seen from the assessment of media and material expert validators, while the readability criteria are seen from the results of student response questionnaires. The results of the study showed that the validity of the product was declared very valid with an average of 94.5% for media experts and 93.7% for material experts. The readability value was considered very good with an average of 89.8%. Based on the research results obtained, it can be concluded that PBL-based e-supplement assisted by Augmented Reality is feasible and has the potential to improve students’ critical thinking skills.